A Novel Oncogenic Role of Inositol Phosphatase SHIP2 in ER‐Negative Breast Cancer Stem Cells: Involvement of JNK/Vimentin Activation. (15th July 2014) - Fu, Chiung‐Hui; Lin, Ruey‐Jen; Yu, John; Chang, Wen‐Wei; Liao, Guo‐Shiou; Chang, Wen‐Ying; Tseng, Ling‐Ming; Tsai, Yi‐Fang; Yu, Jyh‐Cherng; Yu, Alice L.
Abstract Overexpression of SH2‐containing‐5′‐inositol phosphatase‐2 (SHIP2) correlates with poor survival in breast cancer. However, its role in breast cancer stem cells (BCSCs) remains unclear. Here, we showed that the percentage of SHIP2+ cells was positively correlated with that of CD24−CD44+ cells in 60 breast cancer specimens. Among 20 estrogen receptor (ER)‐negative samples, 17 had greater SHIP2 expression in CD24−CD44+ subpopulation than the remaining subpopulation. Data mining of microarray analysis of 295 breast tumors showed a significant correlation of higher SHIP2 expression with distant metastasis. Examination of patient‐derived mouse xenografts revealed that SHIP2 protein and its tyrosine 1135 phosphorylation were significantly higher in BCSCs, identified as CD24−CD44+ or aldehyde dehydrogenase (ALDH+), than non‐BCSCs. SHIP2 silencing or inhibitor of SHIP2 phosphatase significantly decreased mammosphere‐forming efficiency, ALDH+ subpopulation in vitro and tumorigenicity of BCSCs in vivo. Overexpression of SHIP2 enhanced the expression of epithelial–mesenchymal transition markers including vimentin (VIM), which was mainly expressed in ER‐negative breast cancer cells with higher level in mammospheres than monolayer culture. Ablation of c‐Jun N‐terminal kinase 1 (JNK1), JNK2, or VIM diminished the increased ALDH+ population and tumorigenicity, induced by SHIP2 overexpression. BCSCs displayed greater expression of phospho‐JNK than non‐BCSCs and silencing of JNK suppressed SHIP2‐mediated upregulation of VIM. Furthermore, SHIP2 overexpression enhanced Akt activation, but Akt inhibition failed to influence SHIP2‐induced phospho‐JNK/VIM upregulation. In conclusion, SHIP2 plays a key role in BCSCs of ER‐negative breast cancers through activation of Akt and JNK with upregulation of VIM and may serve as a target for therapy directed at BCSCs. Stem Cells2014;32:2048–2060